The Role of Public Administration in the Development of Insertion Firms - Alves Bayern, Marinete (Cuadernos de Trabajo Social, 2012)
This article seeks to give the recognition due to the importance of Insertion Firms, pilot projects which take on the challenge of integrating thousands of people at risk of social exclusion and which comprise a specific type within social and non-profit entities. They come together in autonomous associations and are empowering a sector which is beginning to take off in Spain. Their recognition by Law No. 44/2007 demonstrates their importance in active employment policies, despite the insufficient and uneven support that they receive, which is described in this article. The topic is open to other deeper analyses, but the goal of this article is to give an overview and to draw some conclusions on which areas could continue to be researched with a view toward obtaining more support and commitment from public administration for Insertion Firms.